2018
DOI: 10.1001/jamaoncol.2018.2428
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up Recommendations for Completely Resected Gastroenteropancreatic Neuroendocrine Tumors

Abstract: There is no consensus on optimal follow-up for completely resected gastroenteropancreatic neuroendocrine tumors. Published guidelines for follow-up are complex and emphasize closer surveillance in the first 3 years after resection. Neuroendocrine tumors have a different pattern and timescale of recurrence, and thus require more practical and tailored follow-up. The Commonwealth Neuroendocrine Tumour Collaboration convened an international multidisciplinary expert panel, in collaboration with the North American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 39 publications
4
88
0
Order By: Relevance
“…Given their high proliferative activity and low expression of SSTRs, poorly differentiated NETs are commonly imaged by 18 F‐fluorodeoxyglucose PET/CT. In well‐differentiated NETs 18 F‐fluorodeoxyglucose PET uptake can correlate negatively with prognosis; however, the use of this imaging modality is not routinely recommended …”
Section: Diagnosismentioning
confidence: 99%
See 3 more Smart Citations
“…Given their high proliferative activity and low expression of SSTRs, poorly differentiated NETs are commonly imaged by 18 F‐fluorodeoxyglucose PET/CT. In well‐differentiated NETs 18 F‐fluorodeoxyglucose PET uptake can correlate negatively with prognosis; however, the use of this imaging modality is not routinely recommended …”
Section: Diagnosismentioning
confidence: 99%
“…However, potential benefits and costs of such an approach should be carefully weighted in the context of a usually indolent disease. Postoperative imaging surveillance of radically resected GEP‐NETs can be performed at intervals ranging from every 6 months to every 2 years, depending on the biologic aggressiveness of the neoplasm, as determined by the Ki‐67 index, mitotic activity, degree of differentiation, presence of lymphovascular or perineural invasion, clearance of margins, and quality of the surgery performed . Cross‐sectional imaging (CT or MRI) is considered standard, whereas the routine use of functional imaging is not endorsed .…”
Section: Follow‐upmentioning
confidence: 99%
See 2 more Smart Citations
“…Two randomized control studies and a Cochrane meta-analysis of patients with colorectal cancer demonstrated no OS benefit with a more stringent follow-up protocol including thoracic cross-sectional imaging after surgery [19-21]. Nevertheless, recent recommendations on post-treatment surveillance of resected GEP-NENs based on the risk stratification of established prognostic factors allow for a more individualized, patient-tailored approach [22]. In the light of this knowledge and taking into consideration the indolent but still unpredictable nature of GEP-NENs with a different timescale and pattern to progression, risk stratification for surveillance for the majority of stage IV GEP-NEN patients, particularly those without extrahepatic metastases, can be used to identify patients at a high risk of developing LM.…”
Section: Discussionmentioning
confidence: 99%